Reversible π-system switching of thiophene-fused thiahexaphyrins by solvent and oxidation/reduction. Issue 38 (14th August 2018) - Higashino, Tomohiro; Kumagai, Atsushi; Sakaki, Shigeyoshi; Imahori, Hiroshi
Abstract : The dithieno[3, 4-b:3′, 4′-d]thiophene unit is a new effective motif to realize the π-system switching of expanded porphyrins. Abstract : The concept of chemical topology has generated considerable interest among chemists and one of the state-of-the-art topics is Möbius topology in cyclic π-conjugated molecules. In this regard, expanded porphyrins have been extensively studied because of their facile topological interconversions and attractive optoelectronic properties. A typical example involves [28]hexaphyrins: they show topological conversion between planar Hückel and twisted Möbius topologies owing to their flexible structure. With this in mind, we designed a [28]hexaphyrin where one dimethine pyrrole unit was replaced with dithieno[3, 4- b :3′, 4′- d ]thiophene (β-DTT), aiming at a reversible switching between macrocyclic and cross-conjugated π-systems by a change in molecular topologies. Considering that the β-DTT unit can offer both macrocyclic and cross-conjugated π-circuits, we envisioned that a combination of the topological interconversion of [28]hexaphyrin with the two π-circuits of the β-DTT unit would enable a reversible switching between macrocyclic and cross-conjugated π-circuits on Möbius and Hückel topologies, respectively, by a simple conformational change. Unexpectedly, the hexaphyrin revealed a unique, unprecedented π-system switching between a Möbius cross-conjugated π-system and a Hückel antiaromatic π-system, which was fully supported by both experimental and theoretical investigations. Meanwhile, the [28]hexaphyrin was also found to be redox interconvertible with the corresponding [26]hexaphyrin with a Hückel cross-conjugated π-system. These results demonstrate that the β-DTT unit is a new effective motif to realize π-system switching by changing molecular and π-system topologies. Importantly, external stimuli, i.e., solvent, as well as oxidation/reduction can be used to trigger the topological changes in expanded porphyrins with the help of the β-DTT unit.